Hybrid cements from mining tailings for possible uses in construction - Marllory Isaza-Ruiz; Magali Restrepo-Posada; Harold Cardona-Trujilo; Maryory Astrid Gómez-Botero (Revista Facultad de Ingeniería Universidad de Antioquia)
The Department of Antioquia, Colombia, produces 47% of the mining tailings linked to national gold extraction. These residues, stored in dam-like deposits, contain toxic substances such as heavy metals, posing serious risks to the environment and public health. Due to their high silica and alumina content, these tailings could be repurposed as alternative cementitious materials. Hybrid cements, formed by combining Portland cement with alkaline-activated materials, offer a lower environmental impact and support circular economy practices. In this study, the potential use of Antioquia’s mining tailings as precursors for hybrid cement production was evaluated. Sodium carbonate and sodium silicate were used as alkaline activators, and curing was performed at room temperature. The tailings’ chemical composition showed suitable levels of silica and alumina for geopolymer synthesis. Concrete specimens were prepared using hybrid cement and three types of aggregates: sand, coarse tailings, and recycled polymer. After 28 days of curing, the highest compressive strength was 568.6 kN ± 6.1 with coarse tailings, followed by 550.3 kN ± 7.9 with sand, and 325.3 kN ± 7.5 with recycled polymer. These results demonstrate the feasibility of using mining residues in sustainable construction applications.